Isolation and Test of Pigment Thermostability of Katokon Chili (Capsicum chinense Jacq.) - Puspita, Dhanang; Tjahjono, Josephine Diana; Samalukang, Yunius; Toy, Binerd Anthon Im; Totoda, Norson Willem (University of Brawijaya, 2018)
Chili (Capsicum sp) is one of the agricultural product. Katokon chili (Capsicum chinense Jacq.) is one of the most popular chiliÂ in Toraja-South Sulawesi. Katokon chili has a distinctive aroma and strong spicy flavor. The red color on chili is an indicator of natural pigment content. The aim of this study was to determine the types of pigments in katokon chili and to see the stability of the pigment to the exposure of hot temperature. The method used is pigment extraction using acetone. Pigment analysis was performed with spectotometer UV-Vis and TLC. The thermostability test with the addition of VCO and boiling for 5, 10, 15, and 20 minutes ago was analyzed with spectrophotometer UV-Vis. The result of research, there is 8 color fraction from a result of TLC. Total carotenoids of 0.93 mg / 100 g mg / 100 ml. Carotenoid decline in heating; 0.113164 mg / 100ml (5 min) 0.150986 mg / 100 ml (10 min), 0.099259 mg / 100ml (15 min), and 0.024046 mg / 100 ml (20 min). The colors of the 8 fractions show the characteristics of the compound present in the pigment based on the molecular weight and the polarity. The decrease in carotenoid concentration caused by heat exposure causes the pigment to lose protection from its membrane, so oxidation can occur easily, especially under high-temperature conditions, resulting in the color of the pigment fading.Keyword: chili, carotenoid, pigment, katokon, thermostability.